Menyoal Persahabatan Sebagai Problem Relasionalitas: Sebuah Kontruksi Atas Konsep Alteritas Emanuel Levinas Dan Pluralitas Hannah Arendt - Pius Pandor (Sekolah Tinggi Widya Sasana, 2020)
Alterity, plurality, and relationship are the three key words which summarize the whole content of this article. The first key word is the core of Emanuel Levinas’ Ethics, the second key word is the summary of Hannah Arendt’s the essence of politics, and the third is from the construction on the concepts of alterity and plurality. From the attempt to construct the two concepts, the writer assumes that alterity and plurality are the basis to understand friendship as the problem of a relationship. The method used in this article is hermeneutics on the inter-subjectivity based on Emanuel Levinas’ Ethics and Hannah Arendt’s thought on politics. The findings on this construction is that friendship which is based on the principles of relationship is the solution of the egology – self-enhancement and ‘heterophobia’ – the phobia to other people in the daily life these days.